Ongoing pregnancies in patients with unexplained recurrent pregnancy loss: adverse obstetric outcomes. (3rd July 2019) - Cozzolino, Mauro; Rizzello, Francesca; Riviello, Chiara; Romanelli, Chiara; Coccia Elisabetta, Maria
Abstract: To investigate the incidence of adverse pregnancy outcomes in couples with an unexplained Recurrent Pregnancy Loss (RPL) history, a retrospective cohort study was conducted between 2014 and 2015. The study group (A) included couples with an unexplained RPL, and the control group (B) was composed of couples who attended the Low-Risk Antenatal Unit during the same period. On the other hand, 53 couples were included in the study group (A) and on the other hand, 65 in the control group (B). Women with previous unexplained recurrent pregnancies loss had a significantly increased risk of gestational diabetes with 12 cases (22.6%) in the study group and 3 cases (4.6%) in the control (OR: 6.048; 95% CI: 1.607–22.762; p  = 0.007). A slight increase in the risk of preterm delivery and hepatic cholestasis was observed in the study group (6 cases, 11.3%, in study group and 1 case, 1.5% in the controls (OR: 8.170; 95% CI: 0.951–70.158; p  = 0.0555). Women with a history of RPL delivered more frequently by caesarean section (OR: 3.252; 95% CI: 1.460–7.241; p  = 0.0039). Women with a history of RPL were at an increased risk for adverse pregnancy outcomes, mainly gestational diabetes. Therefore, a closer surveillance during the antenatal period is recommended in this group of patients.